Testing hearing of subnormal children - Edgar F Waldon (Journal of All India Institute of Speech and Hearing, 1970)
Experimental psychologists aid investigators interested in the communicative process began to develop formal test and precision instruments which gave us the tools for hearing measurements. For a long time, puretones have been used for determining the hearing senitivity of adults. The same acoustic signal was later used in the testing of children's hearing. In other words, adult standards were imposed upon children for eliciting response and for the determination of hearing thresholds. A review of the literature would indicate that until recently, techniques for measuring sensitivity of hearing of children were almost non-existent. Audiologists used crude methods to estimate hearing levels. Now we do havea few formal techniques available to serve our purpose.